The Share and Role of Motor Transport in the Energy Market - Jacek Brdulak; Ewelina Florczak (International Journal of Small and Medium Enterprises and Business Sustainability, 2021)
Due to their important role in handling socio-economic processes, transport systems, along with individual branches of transport, are also analyzed in terms of their relationship with the environment, energy consumption, safety, emissions and other dependencies. Transport is considered to be an important component of qualitative changes in socio-economic life in terms of searching for responsible, sustainable relationships between humans and the environment. This also obviously applies to road transport, one of the most important modes of transport. The article deals with such problems as transport in the sustainable development strategy, the demand for energy carriers in car transport, and difficulties in popularizing electromobility in car transport.